Study on macroscopic anatomy and developmental model of pterygopalatine suture - ZHANG Wenyi; CHUNG Miri; XIE Yufan; JIANG Lingyong (Shanghai Jiaotong Daxue xuebao. Yixue ban)
Objective·To analyze the anatomical and macroscopic characteristics of the pterygopalatine suture (PPS) in Chinese population using cone-beam computed tomography (CBCT) technology, and to preliminarily investigate its developmental pattern and its association with the correction of maxillary underdevelopment. Methods·A total of 134 CBCT images, taken from July to August 2023 at Shanghai Ninth People's Hospital, Shanghai Jiao Tong University School of Medicine, were categorized into six age groups. The PPS landmarks were utilized to determine the overall transverse position (XPPS), sagittal position (YPPS), insertion angle (IAP), insertion width of the pyramidal process (IWP), and insertion depth of the pyramidal process (IDP). The pterygomaxillary junction was identified through multiplanar observations. Regression analysis was performed to assess the correlation of these parameters with age and gender, and pairwise comparisons were made to determine the stable age range for parameter changes. Paired t-tests and paired chi-squared tests were conducted to analyze the bilateral parameter differences. Results·Results showed that YPPS and IDP did not exhibit significant correlation with age, whereas XPPS, IAP, IWP, and the incidence of pterygomaxillary fusion were significantly positively correlated with age (P<0.01). Gender differences were only significant for XPPS, with males demonstrating greater values than females (P<0.01). Analysis of age-related trends indicated significant differences in XPPS between group 1 (6 years≤age<9 years) and group 2 (9 years≤age<12 years) (female: P=0.006, male: P=0.004); significant differences in IAP were observed between group 2 and group 3 (12 years≤age<15 years) (P=0.042), with 98.5% of samples having an IAP greater than 45 degrees; IWP differences were significant between group 1 and group 3 (P=0.016), and the pterygomaxillary fusion incidence was significantly different among group 1, 2, and 3 (group 1 vs. 2: P<0.001, group 2 vs 3: P=0.037, group 1 vs 3: P<0.001), with an incidence rate exceeding 90% in adults. No significant bilateral differences were found for all parameters. Conclusion·No significant changes were observed in YPPS and IDP after the age of 6, indicating a trend towards fusion of the maxilla with the pterygoid process. The overall transverse position of the PPS tends to stabilize around 12 years of age, while the IAP and IWP continue to increase and reach stability around 15 years of age,with a sagittal insertion orientation of the pyramidal process into the pterygoid notch.